The Effect Of Star Funds Ownership On Fund Family Performance And Flows: Evidence From Saudi Arabia, Malaysia, Indonesia, And Pakistan - Anas Ahmad Mahmoud Bani Atta
In recent decades, fund families have attracted massive assets with their increasingly popular investment vehicles. Fund families are generally distinguished by their size, in terms of the assets under management (AUM) they manage. The fund family manages and controls the AUM of all individual funds within the fund family. Most families are mixed families, they organise Islamic mutual funds (IMFs) and conventional mutual funds (CMFs). IMFs properties differ from CMFs, the most distinctive feature of IMFs lies in the application of Sharia on their investment. The objective of this thesis is to examine and compare three separate yet complementary dimensions of the fund family. First, The performance and performance persistence of fund families. Second, the flows of fund families. Third, the future performance of star fund families. The sample consists of 70 fund families contain 502 mutual funds (Saudi Arabia 25, Malaysia 20, Indonesia 14, and Pakistan 11 fund families), over the period from 2007 to 2018. The time series analysis, the panel pooled and fixed/random effect regression models, and the contingency table methodology are employed. In the first part, the results find that families take benefits from their advantages and outperformed the market benchmarks, Islamic fund families outperformed conventional fund families. Results also find that families are used their strategies and attributes to improve performance. Finally, the results provide evidence about the performance persistence, but it was short and only up to one month. In the second part, the results find an asymmetric response in fund family flows, star fund family attracts more flows, while the poor fund family is not faced with money withdrawal. Results also find that the fund family attributes carry significant weight in the investment decision. Lastly, for the spillover effect, there is an asymmetric response in the flows of peer funds to the presence of Islamic star and poor performing funds in the fund family, while don't find the same asymmetric response for conventional star and poor performing funds. In the third part, the results find a positive persistence performance on fund-family when investors select a fund from a star fund ownership family. Results also find fund families with star fund holding have a capability to persistently hold star fund in the future. This study contributes significantly by providing beneficial information about fund families to investors, regulators, and managers. The results show the fund family performance and characteristics information are important for investors to help them make fund investment decision making. The results will help fund family managers to design the best strategies to attract more money flows, and motivate them to lunch more Islamic funds. The results provide an indicator that regulators should encourage fund management companies to make fund family ranking information available in addition to mutual fund ranking.